2004
DOI: 10.1111/j.1468-5906.2004.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Church Attendance Really Increase Schooling?

Abstract: This article shows that religiosity during adolescence has a significant effect on total number of years of schooling attained. It differs from previous research by focusing on church attendance rather than on denomination and by controlling more completely for the effects of omitted-variables bias. Any estimated correlation between church attendance and schooling without such controls may reflect unmeasured family, community, and individual characteristics. The size of the effect for individuals who attended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 29 publications
2
54
0
4
Order By: Relevance
“…However, religion is also associated with more education, which reduces female fertility. A positive effect of religious attendance during adolescence on education has been documented before (Loury, 2004). In the NLSY the correlation of educational attainment is .167 with religious attendance in 1979/82 but only .134 with religious attendance in 2000 (N = 7537).…”
Section: Discussionmentioning
confidence: 89%
“…However, religion is also associated with more education, which reduces female fertility. A positive effect of religious attendance during adolescence on education has been documented before (Loury, 2004). In the NLSY the correlation of educational attainment is .167 with religious attendance in 1979/82 but only .134 with religious attendance in 2000 (N = 7537).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, we will control for (maternal) education, which has been found to be related to child-rearing practices (Deković 1991;Rispens, Hermans, and Meeus 1996) and aspects of religion (Alwin and Jackson 1982;Keysar and Kosmin 1995;Lehrer 1999;Loury 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Further, other studies have shown that religious service attendance is positively associated with school completion and educational attainment among adolescents and young adults (Beyerlein 2004;Evans et al 1992;Loury 2004;Muller and Ellison 2001;Ribar 1994). Yet, investigations focusing on the educational attainment of sectarian Protestants and people subscribing to fundamentalist beliefs in scriptural inerrancy consistently show that these groups take a hostile stance towards education (Deckman 2004;Sikkink 1999), and have lower rates of educational attainment (Darnell and Sherkat 1997;Fitzgerald and Glass, 2008;Glass and Jacobs 2005;Lehrer 1999;Sherkat and Darnell 1999;).…”
Section: Education Religion and Mortalitymentioning
confidence: 94%